Pelatihan Pembuatan dan Pengaplikasian Trainer Mikrokontroller Atmega2560 - indrawati, elsanda merita; Sari, Kartika Rahayu Tri Prasetyo; Puspitasari, M. Dewi Manikta; Maulidina, Miftakhul; Suwardono, Agus; Riyanto, Indra (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Trainer microcontroller Atmega2560 is a learning media used to run DC motor control programs, stepper motor control, traffic light modules, piezo speaker modules, 4 x 4 keypad modules, 20 x 4 LCD modules with I2C, 32 x 8 pixel matrix modules with MAX7219, 8 digit 7 segment Display with MAX7219. The problem that occurs in the field is that many users are able to run the Trainer Microcontroller Atmega2560 but do not know how to make the Trainer Microcontroller Atmega2560, so this training is expected to increase the knowledge and creativity of users in designing the Trainer Microcontroller Atmega2560. The object of this community service activity is for teachers and students in the field of electrical engineering. The method used in the implementation of community service activities is training and mentoring by adopting classroom action research. The results of this activity are (1) the knowledge and skills of participants involving teachers and students increase in designing the Trainer Microcontroller Atmega2560; and (2) participants' knowledge involving teachers and students increased in running the running LED program, traffic light, DC motor, dot matrix, seven segment, and piezo speaker, and LCD program on the Trainer Microcontroller Atmega2560.